First exposure to general surgery (McGraw-Hill, 2007)
Just what you need for your rotation in general surgery, this unique text puts mastery of the clerkship at your fingertips. Written by doctors who made general surgery their specialty, FIRST EXPOSURE TO GENERAL SURGERY CLERKSHIP is the book they wish they'd had for their GS clerking